Glycemic Profiles of Healthy Individuals with Low Fasting Plasma Glucose and HbA1c. (8th December 2011) - Nomura, Kyoko; Saitoh, Tomoyuki; Kim, Gwang U.; Yamanouchi, Toshikazu
Abstract : Scant data exists on glucose profile variability in healthy individuals. Twenty-nine healthy subjects without diabetes (86% male; mean age, 38 years) were measured by a CGM system and under real-life conditions. The median percentage of time spent on the blood glucose >7.8 mmol/L for 24 hrs was greater than 10% in both NFG and IFG groups. When subjects were divided into either NFG group (i.e., FPG levels of <5.6 mmol/L;n = 22 ) or IFG group (FPG levels of 5.6–6.9 mmol/L;n = 7 ), all CGM indicators investigated but GRADE scores, including glucose variability measures, monitoring excursions, hyperglycemia, hypoglycemia, and 24-hour AUC, did not differ significantly between the two groups. GRADE score and its euglycemia% were significantly different between the two groups. Among various CGM indicators, GRADE score may be a sensitive indicator to discriminate glucose profiles between subjects with NFG and those with IFG.